Strategi Pengembangan Area Traffic Control System (ATCS) dalam Mendukung Smart Mobility di Kota Samarinda - Zaqueena Prinanindya; Sri Sartika; Aldi Dinata Saputra; Faris Risyadi; Fajar Apriani (Social Science Academic, 2026)
Samarinda faces increasingly complex urban mobility challenges, with over 1.01 million registered vehicles, only 881 kilometers of roads, and approximately 1,000 new vehicles added monthly. In response, the Samarinda City Government has implemented the Area Traffic Control System (ATCS) under the Smart City Plus Masterplan 2022–2025. This study analyzes ATCS implementation through SWOT analysis based on field data from interviews with the Head of Road Traffic Division, Samarinda Transportation Agency. Results show that of 41 mapped intersections, 26 have active ATCS cameras installed at strategic locations including Simpang Lembuswana and Fly Over Juanda. Key strengths include strong regulations and an operational control room, while weaknesses encompass insufficient human resources with no night shift rotation, inter-agency camera duplication, and lack of electronic traffic enforcement integration. The greatest opportunity lies in Samarinda’s role in the IKN Tri-City Development Plan and its AI Power City target. The recommended WO strategy prioritizes human resource development, infrastructure duplication resolution, and integrated public transport development.